Der DGB und die Außenpolitik der Bundesregierung zum östlichen Europa unter besonderer Berücksichtigung der deutsch-polnischen Beziehungen in den achtziger Jahren - Świder, Małgorzata (Instytut Historii im. Tadeusza Manteuffla Polskiej Akademii Nauk, 2024)
The involvement of the German Confederation of Trade Unions (DGB) in Ostpolitik is closely tied to the politics of German Social Democracy. Alongside this party, the DGB has gone through all stages of its development. The DGB played a significant role in the 1980s when Poland faced a severe economic, social, and political crisis. During this time, the DGB established extensive contacts with Solidarity and the opposition, utilising its organisational expertise, international connections (including ties to Moscow), and people-to-people interactions. As a result, it became an important partner for the federal government in shaping bilateral Polish-German relations.
p. 121-147
Summary in English and Russian.
Keywords: Ostpolitik; DGB; West German foreign policy; trade unions; Eastern bloc; German-Polish relations; Deutscher Gewerkschaftsbund; Labor unions - political activity - Germany (West) - history - 20th century; Germany (West) - foreign relations - Poland - 1970-2000; Poland - foreign relations - Germany (West) - 1970-2000